Tetrapod-track taphonomic modes (TTTM) applied to Triassic lacustrine systems from southern South America. (December 2022) - Mancuso, Adriana Cecilia; Marsicano, Claudia A.; Krapovickas, Veronica
Abstract: Tetrapod-track taphonomic modes (TTTM) have been used recently as sensitive indicators of paleoenvironmental and paleoclimatic conditions during deposition and imprinting of the track-bearing beds in an underfilled lake basin from NW Argentina. Three tetrapod track preservation modes were defined based on the fidelity of preservation of anatomical features: a High Fidelity Mode shows sharp and detailed impressions of the digits and palms, with the clear impression of the print walls; a Moderate Fidelity Mode shows impressions of digits and palms that have little detail of the anatomy of the trackmaker's autopodia; and finally, a Low Fidelity Mode characterized by oval or irregular depressions with outlines surrounded by deep and distinct rims of displaced sediment. In this contribution, we expand our initial TTTM approach to all three lake-basin types: underfilled, balanced-fill, and overfilled. We review the Triassic tetrapod track record preserved in several lacustrine deposits of three continental basins from central-western Argentina and Patagonia. Our results show that our TTTM are consistently expressed in the different lake basins analyzed, and that substrate rheology it is not only a function of water content, but also of grain-size distribution (sand:clay ratio), the type of clay minerals, and stratal stacking at the bed scale. Linking tetrapod-track taphonomic modes to the lake-basin-type framework places observations of vertebrate traces into a broader context of depositional systems, landscape evolution, and climate and tectonic changes. Highlights: In this contribution, we explore our tetrapod-track taphonomic modes (TTTM) to all three lake-basin types: underfilled, balance-fill, and overfilled. Our results show that our TTTM are consistently expressed in the different lake basins analyzed, and that substrate rheology it is not only a function of water content, but also of grain-size distribution (sand:clay ratio), the type of clay minerals, and stratal stacking at the bed scale. Linking tetrapod-track taphonomic modes to the lake-basin-type framework places observations of vertebrate traces into a broader context of depositional systems, landscape evolution, and climate and tectonic changes.